Global Jihad and America : the hundred-year-war beyond Iraq and Afghanistan - Hashmi, Taj ul-Islam, 1948- (New Delhi : SAGE, 2016)
This study questions the assumption if Islamist terrorims of'Global Jihad' poses the biggest threat to modern civilization in the East and West. If the Islamic and Western civilizations being'incompatible' to each other are destined to be a loggerheads for an indefinite period is another area of investigation. This book argues that the world is fast entering the post-terrorist phase of modern history.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 22, 2016).
Keywords: Terrorism -- United States -- Prevention; War on Terrorism, 2001-2009.; Islamic fundamentalism; Islamic countries -- Relations -- Western countries